Development of fish hamburger with reduced sodium content using sweet passion fruit shell flour - SILVA, Iris Laura Lima da; COUTINHO, Juliane dos Santos; GOES, Elenice Souza dos Reis; TOBAL, Thaise Mariá (Food Science and Technology, 2023)
Fish burgers were developed with the substitution of sodium chloride (NaCl) by using sweet passion fruit peel flour. Tambacu (a Brazilian freshwater fish) burgers were prepared with a 50% reduction of sodium chloride and an addition of 0, 3.1, 3.7, and 4.3% of sweet passion fruit peel flour. The burgers with higher levels of flour were less hard and less elastic and required less chewing to be swallowed. Significantly lower ash and sodium contents were found in the formulations in which flour was used. The formulations did not differ concerning the color and aroma, as well as texture, flavor, and overall impression. The burger with 0% flour have greater acceptance when compared to the other fish burgers, which did not differ from each other in sensory characteristics, obtaining scores corresponding to the descriptions of liked moderately and liked slightly. The partial substitution of NaCl by using sweet passion fruit peel flour resulted in fish burgers with reduced sodium content and good physical and sensory characteristics, demonstrating the potential demand for its use.